An Analysis Of Deixis On The Song Lyrics Of “Emails I Can’t Send” By Sabrina Carpenter: English - Ambarita, Mika; Hutahaean, David Togi; Rohana Sinaga, Asima (Innovative: Journal Of Social Science Research, 2024)
The researcher intended this research to discover the types of Deixis mainly in Person Deixis types in the Emails I Can’t Send album by Sabrina Carpenter. This research used descriptive qualitative which the data were obtained through the Spotify application. The subject of this research was the lyrics in the album. The data collection instrument takes a note to look carefully, and the data directed in finding the Person Deixis on the album to the desired data. The result of this research showed that the album used 573 First Person types with a percentage of 53%, 338 Second Person types with a percentage of 31%, and 166 Third Person with a percentage of 16%. To analyze the data, the researcher used the Flitto app. According to the album, the researcher concluded that the album, First Person type was dominant in the song lyrics to express the singer's feelings. The Second Person and the Third Person types in the song are used to express what they are doing to the First Person type.